Pendampingan Penggunaan LaTeX untuk Penulisan Artikel Ilmiah bagi Dosen Universitas PGRI Palembang - Yusuf Hartono; Somakim Somakim; Weni Dwi Pratiwi; Jeri Araiku; Zuli Nuraeni (Jurnal Anugerah, 2019)
This community service activity aims to train lecturers of Universitas PGRI Palembang in writing scientific article, making presentation, and mathematics equations using LaTeX application, as well as understanding their responses toward the activity. This activity conducted employing assisting model with sharing tools, materials, and demonstration method, whereas 23 participants from different faculties joint the training. The response shows very positive satisfaction for all indicators with the range of 86% - 94%. The highest response is on the importance of the program, while time efficiency item scored 86%. All participants wish for sustainable training with longer time period.